Evaluating Usability Theory Of WWW In Malaysia - Wan Mohd Isa, Wan Abdul Rahim (2005)
The aim of this report is to identify the usability of application theory for the World Wide Web. It also assesses the application of usability in the web page development, in order to provide suggestions to the industries for the better use of their web pages. The purpose of the descriptive study is to provide some guidelines to the web developers.